The Impact of Tourism on the Economic Growth of African Countries - Arain, Eamaan Azhar (2017)
Tourism has been known to have an impact on the economy of the country. This study aims to identify the effect of tourism on the economic growth of African countries taking annual data from the World Bank from 2003-2013. Pedroni’s Panel Cointegration and Dumitrescu and Hurlin (2012) Granger Causality test is employed to determine the relationship. In addition, two proxies are used for tourism, tourism receipts and tourism arrivals, to act as robustness tests. The sample is also grouped into island and non-island countries and FMOLS estimation is done to try to determine the elasticities of the variables that are in the study and study whether there is a difference between island or non-island countries. The effect of tourism reliance is also examined by introducing an index that measures tourism reliance. The empirical results indicate that there is a cointegrating relationship between tourism and economic development. In addition, the causality is uni-directional from GDP to tourism in the case of the first proxy for tourism, (tourism receipts) and the causality is bi-directional in the case of the second proxy of tourism (tourism arrivals)